Tunnel Vision: A Novel Approach for Blood Clot Retrieval Using Cryotherapy through a Flexible Bronchoscope - Fernando Figueroa Rodriguez; Parminder Minhas; Houssein A. Youness (Case Reports in Pulmonology)
Cryoprobes inserted through a bronchoscope in the airways have frequently been used for the removal of foreign bodies and clots. We present a case of a 72-year-old man who presented with COVID-19 pneumonia and respiratory failure, requiring intubation and proning. During his stay, he developed pneumothoraces in the left hemithorax, which necessitated the placement of two large-bore chest tubes. However, the pneumothorax recurred. There was no air leak in either chest tube, and attempts to restore their patency through flushing or suctioning were unsuccessful. A disposable flexible bronchoscope was inserted into the chest tubes, allowing visualization of the source of occlusion and identification of a blood clot obstructing both tubes. These clots were successfully removed using a cryoprobe inserted through the working channel of the bronchoscope, leading to the restoration of chest tube patency and resolution of the pneumothorax.